Gamified flipped learning in a French foreign language class: Efficiency and student perception - Anane, Chiraz (Frontiers in Education, 2022)
To enhance the students’ engagement in a French as foreign language course, two active learning methods were combined: Flipped Learning (FL) and gamification. This study aims to explore the efficiency of these teaching methods in a foreign language course with beginner learners and to assess the students’ perception of this experience. 215 students were enrolled in this university elective course. All sections were taught by the same instructor and during the same semester. All students experienced flipped learning methodology as well as a traditional teaching methodology. The results indicate that the students’ scores in the gamified quizzes were better when they prepared in advance for the sessions and had a flipped learning session. Moreover, in a questionnaire completed at the end of the term, students mentioned that they preferred the FL sessions as it helped them to better understand and memorize the material. They also appreciated the use of gamification tools that helped them to learn.